NEU1—A Unique Therapeutic Target for Alzheimer’s Disease - Khan, Aiza; Sergi, Consolato M. (Frontiers in Pharmacology, 2022)
Neuraminidase 1 (NEU1) is considered to be the most abundant and ubiquitous mammalian enzyme, with a broad tissue distribution. It plays a crucial role in a variety of cellular mechanisms. The deficiency of NEU1 has been implicated in various pathological manifestations of sialidosis and neurodegeneration. Thus, it is a novel therapeutic target for neurodegenerative changes in Alzheimer’s brain. However, to manipulate NEU1 as a therapeutic target, it is imperative to understand that, although NEU1 is commonly known for its lysosomal catabolic function, it is also involved in other pathways. NEU1 is involved in immune response modulation, elastic fiber assembly modulation, insulin signaling, and cell proliferation. In recent years, our knowledge about NEU1 has continued to grow, yet, at the present moment, current data is still limited. In addition, the unique biochemical properties of NEU1 make it challenging to target it as an effective therapeutic option for sialidosis, which is a rare disease but has an enormous patient burden. However, the fact that NEU1 has been linked to the pathology of Alzheimer’s disease, which is rapidly growing worldwide, makes it more relevant to be studied and explored. In the present study, the authors have discussed various cellular mechanisms involving NEU1 and how they are relevant to sialidosis and Alzheimer’s disease.